Controlled dendrimersome nanoreactor system for localised hypochlorite-induced killing of bacteria - Potter,M; Najer,A; Kloeckner,A; Zhang,S; Holme,MN; Nele,V; Che,J; Penders,J; Saunders,C; Doutch,JJ; Edwards,A; Ces,O; et al. (ACS Nano, 2020)
Antibiotic resistance is a serious global health problem necessitating new bactericidal approaches such as nanomedicines. Dendrimersomes (DSs) have recently become a valuable alternative nanocarrier to polymersomes and liposomes due to their molecular definition and synthetic versatility. Despite this, their biomedical application is still in its infancy. Inspired by the localized antimicrobial function of neutrophil phagosomes and the versatility of DSs, a simple three-component DS-based nanoreactor with broad-spectrum bactericidal activity is presented. This was achieved by encapsulation of glucose oxidase (GOX) and myeloperoxidase (MPO) within DSs (GOX-MPO-DSs), self-assembled from an amphiphilic Janus dendrimer, that possesses a semipermeable membrane. By external addition of glucose to GOX-MPO-DS, the production of hypochlorite (−OCl), a highly potent antimicrobial, by the enzymatic cascade was demonstrated. This cascade nanoreactor yielded a potent bactericidal effect against two important multidrug resistant pathogens, Staphylococcus aureus (S. aureus) and Pseudomonas aeruginosa (P. aeruginosa), not observed for H2O2 producing nanoreactors, GOX-DS. The production of highly reactive species such as –OCl represents a harsh bactericidal approach that could also be cytotoxic to mammalian cells. This necessitates the development of strategies for activating –OCl production in a localized manner in response to a bacterial stimulus. One option of locally releasing sufficient amounts of substrate using a bacterial trigger (released toxins) was demonstrated with lipidic glucose-loaded giant unilamellar vesicles (GUVs), envisioning, e.g., implant surface modification with nanoreactors and GUVs for localized production of bactericidal agents in the presence of bacterial growth.